Problem Solving Ability of Senior High School Students Based on Self-Regulation in Instagram-Assisted Brain-Based Learning - Damayanti, Taulia; Mastur, Zaenuri; Masrukan, Masrukan (Unnes Journal of Mathematics Education Research, 2021)
The main objective of this study was to describe the mathematics problem solving abilities of senior high school students based on self-regulation in Instagram-assisted Brain-Based Learning. This research is a mixed methods model concurrent embedded. The population was 10th grade students of SMA N 1 Nalumsari in the 2016/2017 school year. The selection of research subjects based on self-regulation was done purposively using the Self-Regulation of Learning Self-Report Scale (SRL-SRS). Subjects were categorized into four categories: students with self-regulation dominant planning, self-monitoring, evaluation, and reflection. Subjects were 11 students consisting of 3 students each for the planning, self-monitoring, and reflection categories, and 2 students for evaluation. The findings show that in an effective Instagram-assisted Brain-Based Learning setting, the problem solving abilities of subjects from various categories of self-regulation were diverse. Most subjects are able to master indicators of problem solving abilities in easy and medium difficulty problems. On problem with a high difficulty level, 1 planning student, 2 self-monitoring students, 2 evaluation students, and 3 reflection students have not been able to apply and adapt a variety of appropriate strategies to solve problems.